Molecular dynamic simulations to assess the structural variability of ClpV from Enterobacter cloacae - Motiwala, Tehrim; Nyide, Babalwa; Khoza, Thandeka (Frontiers in Bioinformatics, 2025)
The Enterobacter cloacae complex (ECC) consists of six Enterobacter species (E. cloacae, hormaechei, kobei, ludwigii, nimipressuralis and asburiae) that have emerged as nosocomial pathogens of interest, with E. cloacae and Enterobacter hormachei being the most frequently isolated ECC species in human clinical specimens and intensive care unit (ICU) patients. Many nosocomial outbreaks of E. cloacae have been related to transmission through contaminated surgical equipment and operative cleaning solutions. As this pathogen evades the action of antibiotics, it is important to find alternative targets to limit the devastating effects of these pathogens. ClpV is a Clp ATPase which dissociates and recycles the contracted sheath of the bacterial type VI secretion system (T6SS), thereby regulating bacterial populations and facilitating environmental colonization. Seventy-one Enterobacter strains were mined for Clp ATPase proteins. All the investigated strains contained ClpA, ClpB, ClpX and ClpV while only 20% contained ClpK. All the investigated strains contained more than one ClpV protein, and the ClpV proteins showed significant variations. Three ClpV proteins from E. cloacae strain E3442 were then investigated to determine the structural difference between each protein. Homology modelling showed the proteins to be structurally similar to each other, however the physicochemical characteristics of the proteins vary. Additionally, physicochemical analysis and molecular dynamic simulations showed that the proteins were highly dynamic and not significantly different from each other. Further investigation of the proteins in silico and in vitro in the presence and absence of various ligands and proteins could be performed to determine whether the proteins all interact with their surroundings in the same manner. This would allow one to determine why multiple homologs of the same protein are expressed by pathogens.